2022
DOI: 10.3389/fgene.2022.952083
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential models for predicting progestin insensitivity in patients with endometrial atypical hyperplasia and endometrioid endometrial cancer based on ATAC-Seq and RNA-Seq integrated analysis

Abstract: Objective: The aim of this study was to establish predictive models based on the molecular profiles of endometrial lesions, which might help identify progestin-insensitive endometrial atypical hyperplasia (EAH) or endometrioid endometrial cancer (EEC) patients before progestin-based fertility-preserving treatment initiation.Methods: Endometrial lesions from progestin-sensitive (PS, n = 7) and progestin-insensitive (PIS, n = 7) patients were prospectively collected before progestin treatment and then analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The lower TMB in the MSI-H subgroup when compared to the POLE mut subgroup may be correlated with the difference in long-term treatment efficacy between the two groups. Recently, Hu et al reported that the expression of PDGFC, DIO2, SOX9, and BCL11A was upregulated in progesterone-insensitive endometrial lesions when compared with progesterone-sensitive endometrial lesions, while the expression of FOXO1, IRS2, APOE, FYN, and KLF4 was downregulated, as based on the integrated analysis of ATAC-Seq and RNA-Seq (25). By conducting differential gene enrichment analysis of TCGA data (the analytical data were not presented in this article), we found that the expression of IRS2 was downregulated in POLE mut and MSI-H groups of EC patients compared with the TP53 wt group.…”
Section: Molecular Characteristics and The Outcomes Of Conservative T...mentioning
confidence: 99%
“…The lower TMB in the MSI-H subgroup when compared to the POLE mut subgroup may be correlated with the difference in long-term treatment efficacy between the two groups. Recently, Hu et al reported that the expression of PDGFC, DIO2, SOX9, and BCL11A was upregulated in progesterone-insensitive endometrial lesions when compared with progesterone-sensitive endometrial lesions, while the expression of FOXO1, IRS2, APOE, FYN, and KLF4 was downregulated, as based on the integrated analysis of ATAC-Seq and RNA-Seq (25). By conducting differential gene enrichment analysis of TCGA data (the analytical data were not presented in this article), we found that the expression of IRS2 was downregulated in POLE mut and MSI-H groups of EC patients compared with the TP53 wt group.…”
Section: Molecular Characteristics and The Outcomes Of Conservative T...mentioning
confidence: 99%